CASE STUDY OF NEWCASTLE DISEASE VELOGENIC STRAIN WITH MULTIORGAN LESSIONS IN VACCINATED BROILER IN SUSUT, BANGLI - I Gde Andhika Putra Pratama,; Mahardika, I Gusti Ngurah Kade; Winaya, Ida Bagus Oka; Besung, I Nengah Kerta; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2025)
Newcastle disease (ND) is a highly contagious viral disease of poultry with high mortality rates in velogenic strains. This paper present findings about velogenic strain of Newcastle disease in case study. The methods used in examination of animal case are observation, anatomical pathology examination, histopathology examination, TAB cultivation, serological tests, bacterial identification and parasite identification. In this case study, 28-day-old broiler chickens were obtained from a farmer in Demulih Village, Susut, Bangli. The clinical symptoms observed in the affected chickens included weakness, anorexia, difficulty breathing, greenish-white diarrhea, and torticollis. Pathological anatomical examination revealed congestion in the brain, hemorrhages in the trachea, lungs, heart, and intestines, as well as petechiae in the proventriculus. Histopathological examination showed inflammatory changes were dominated marked by mononuclear cell infiltration in the brain, trachea, lung, heart, proventriculus and intestine. Result of TAB cultivation continued with using HA test showed that virus can agglutination erythrocytes with titer 210 HA Unit. ND virus was confirmed by HI test. Based on this case study, it was concluded that the chickens were infected with ND.